2014
DOI: 10.1002/anie.201309987
|View full text |Cite
|
Sign up to set email alerts
|

Substrate‐Directed Hydroacylation: Rhodium‐Catalyzed Coupling of Vinylphenols and Nonchelating Aldehydes

Abstract: We report a protocol for branched-selective hydroacylation of vinylphenols with aryl, alkenyl and alkyl aldehydes. This cross-coupling yields α-aryl ketones that can be cyclized to benzofurans, and it enables access to eupomatenoid natural products in four steps or less from eugenol. Excellent reactivity and high levels of branched regioselectivity are obtained. We propose that aldehyde decarbonylation is overcome by using an anionic directing group on the olefin and a small bite-angle diphosphine ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 66 publications
0
32
0
1
Order By: Relevance
“…1 For the hydroacylation of olefins, intramolecular version of the reaction has been effectively used to form cyclic ketone products. 2 Since the pioneering reports on the intermolecular hydroacylation of olefins, 3 a number of late transition metal catalysts have been found to mediate anti -Markovnikov hydroacylation of alkenes to form the linear ketones. 4–6 One of the most debilitating problems on the olefin hydroacylation reaction resides in competing decarbonylation of aldehyde substrates, which often leads to the deactivation of metal catalysts.…”
mentioning
confidence: 99%
“…1 For the hydroacylation of olefins, intramolecular version of the reaction has been effectively used to form cyclic ketone products. 2 Since the pioneering reports on the intermolecular hydroacylation of olefins, 3 a number of late transition metal catalysts have been found to mediate anti -Markovnikov hydroacylation of alkenes to form the linear ketones. 4–6 One of the most debilitating problems on the olefin hydroacylation reaction resides in competing decarbonylation of aldehyde substrates, which often leads to the deactivation of metal catalysts.…”
mentioning
confidence: 99%
“…A presença de grupos diretores nos substratos foi utilizada com sucesso para controlar a seletividade de hidrogenações, 45,46 e esse conceito tem sido expandido para hidrosililação, 47 hidroboração 48 e hidroacilação, 49 em que um substituinte polar orienta a qual carbono será ligado o grupo funcional. Apesar dos avanços na reação de hidroaminação, o uso de grupos diretores para essa transformação ainda é raro.…”
Section: Síntese De Aminas Quirais Com Estereocentros Nas Posições αunclassified
“…11 Recently, Dong et al reported the rhodium-catalyzed coupling of vinylphenols and nonchelating aldehydes. 12 Another approach from 2-methoxychalcone epoxides has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13]16 Few groups reported the synthesis of eupomatenoid-6. 10,11,13,16 Although many synthetic methods have been reported in the literature, procedures for the construction of benzofuran motif via the formation of 2-alkoxydeoxybenzoin are highly desirable.…”
mentioning
confidence: 99%